Water quality in the ecosystem of sea cucumber Acaudina sp. in the Delta Wulan Waters, Central of Java, Indonesia. Issue 1 (April 2021) - Widianingsih, W; Nuraeni, R A T; Hartati, R; Endrawati, H; Sugianto, D N; Mahendrajaya, R T
Abstract: Sea cucumber Acaudina sp. is one of the benthic animals which has a very important role for the benthic ecosystem in a waters. One of its roles is to maintain sediment stability and is also known as a bioturbation animal. The research aims are to study the water quality in the ecosystem of sea cucumber in the Delta Wulan Waters, Demak. The research was conducted for 4 months (May, June, July and August 2020). Based on the research result, the type of substrate in the Delta Wulan Waters is silt has a range 87.4–96.70%. The salinity has a range value is 29.25 to 33.50 ppt. The value of the water temperature is 28.6–29.9 °C. The DO value has a range is 5.04–8.13 ppm. The pH value range is 6.05–7.–56. Furthermore, the average concentration of Pb in sediment has range 4.775.10 mg/kg. The average concentration of Cu in sediment has range 15.93–16.06 mg/kg. The average concentration of Cd in sediment has range 0.02–0.07 mg/kg. In the sediment, the average concentration of ortho-phosphate content has range 0.014–0.027 mg/g, nitrate has range 0.035–0.073 mg/g and chlorophyll-a has range 268-805 mg/m 2 . In conclusion, water quality in Delta Wulan Waters can still support population growth of Acaudina sp..